Book reviews - Kičaitė, Asta; Peldschus, F. (Journal of Civil Engineering and Management, 2010)
LOW POROSITY BUILDING CERAMICS PRODUCED FROM LOCAL TECHNOGENIC RAW MATERIALS(R. Mačiulaitis, R. Žurauskiene. Mažo poringumo statybine keramika iš vietiniu ir technogeniniu žaliavu. Vilnius: Technika, 2007. 220 p. ISBN 978–9955–28–203–7)MEHRZIELSELEKTION FÜR ENTSCHEIDUNGEN IM BAUWESEN(E. K. Zavadskas, A. Kaklauskas. Multiple objective selection for decisions in civil engineering) Fraunhofer IBR Verlag 2007, Schriftenreihe Planung, Technologie, Management und Automatisierung im Bauwesen, ISBN 978–3‐8167–7203–3.First Published Online: 14 Oct 2010